Alzheimer S Disease: Redox Dysregulation as a Common Denominator for Diverse Pathogenic Mechanisms - Eugenin-Leon, J (2012)
Alzheimer s disease (AD) is the most common cause of dementia and a progressive neurodegeneration that appears to result from multiple pathogenic mechanisms (including protein misfolding/aggregation, involved in both amyloid ?-dependent senile plaques and tau-dependent neurofibrillary tangles), metabolic and mitochondrial dysfunction, excitoxicity, calcium handling impairment, glial cell dysfunction, neuroinflammation, and oxidative stress. Oxidative stress, which could be secondary to several of the other pathophysiological mechanisms, appears to be a major determinant of the pathogenesis and progression of AD. The identification of oxidized proteins common for mild cognitive impairment and AD suggests that key oxidation pathways are triggered early and are involved in the initial progression of the neurodegenerative process. Abundant data support that oxidative stress, also considered as a main factor for aging, the major risk factor for AD, can be a common key element capable of articulating the divergent nature of the proposed pathogenic factors. Pathogenic mechanisms influence each other at different levels. Evidence suggests that it will be difficult to define a single-target therapy resulting in the arrest of progression or the improvement of AD deterioration. Since oxidative stress is present from early stages of disease, it appears as one of the main targets to be included in a clinical trial. Exploring the articulation of AD pathogenic mechanisms by oxidative stress will provide clues for better understanding the pathogenesis and progression of this dementing disorder and for the development of effective therapies to treat this disease. © 2012, Mary Ann Liebert, Inc.